Athens : the city as university - Livingstone, Niall (Milton Park, Abingdon, Oxon : Routledge, 2017)
"Athens has been synonymous with the life of the intellect, and Athens : A University City tells you just why. It is more than a history of education in terms of curriculum and shows the position of education and ideas in ancient Athens as a whole, providing an understanding of Athenian intellectual culture across the whole social range, and within its socio-political context"--Provided by publisher.
Part 1. Setting the stage for citizens -- Introduction: Democratic knowledge -- Citizens modern and ancient -- Democracies -- Intellectual attainment and democratic ideals -- Myth and Mousike -- Heroic politics -- Hesiod's poetics of struggle -- Solon : accommodating Athens to the muse -- Part 2. Citizen spaces -- Knowing where it happens -- Democratic citizenship : staging and rehearsal -- What did citizens learn? -- Learning at home -- Places of learning -- The Agora -- The view beyond the city -- In and out of the barber's shop -- Part 3. The citizen performer -- Writing the city -- Suspicion of writing in Athens -- On writers (people who write written speeches, or Sophists) -- The argument of "on writers" -- A misdirected attack on writing? -- The two faces of the writer -- Stylish spontaneity -- Conclusion: The city as university.
Includes bibliographical references and index.
Includes bibliographical references.
Keywords: Athens (Greece) -- Intellectual life; Education, Higher -- Greece -- Athens -- History -- To 1500.; Learning and scholarship -- Greece -- Athens -- History -- To 1500.; Greek literature -- History and criticism; Citizenship -- Greece -- Athens -- History -- To 1500.; Democracy -- Greece -- Athens -- History -- To 1500.; Political culture -- Greece -- Athens -- History -- To 1500.; Athens (Greece) -- Politics and government; Athens (Greece) -- Social life and customs; Greece -- History -- To 146 B.C.